Direct Analysis of Infant Formula Via Laser Induced Breakdown Spectroscopy - Ismail, Hanif (Enhanced Knowledge in Sciences and Technology, 2022)
For infant consumers’ healthy and strong growth, the quantity of nutrition in the infant formula must be controlled. Therefore, the work presented here aims to analyse an elemental composition in infant formula. In order to analyse the nutritional value in infant formula, we proposed employing the laser induced breakdown spectroscopy (LIBS) approach combined with principal component analysis (PCA) as their analysing tool to directly study elemental composition in infant formula. PCA results shows the first principal component accounts for around 83.3 percent of total variation, while the second principal component accounts for nearly 15.2 percent. The PC1 is defined by Calcium and Sodium elements, whereas the PC2 is characterised by Magnesium and Potassium elements, according to NIST database mapping and PCA analysis. The components appear to play a major role in the nutritional value of infant formula. We can clearly state that the LIBS technique is useful and capable of analysing elemental composition of infant formula and demonstrating its capacity for real-time direct analysis of food sample.